Evaluation of lymphoma patients after hematopoetic stem cell transplantation in terms of early period cardiotoxicity development - Çelikçi, Sedat; Ozkocaman, Vildan; Yaman, Fatih; Özkalemkaş, Fahir (The European Research Journal, 2023)
Objectives: Autologous hematopoietic stem cell transplant (AHSCT) following high-dose chemotherapy in recurrent lymphomas has become the standard treatment. However, this method leads to various toxic side effects, including cardiotoxicity. This study aims to determine the factors that may cause post-transplant cardiotoxicity. Methods: A total of 35 patients older than 18 years old, diagnosed with recurrent lymphoma, who underwent AHSCT at the Uludağ University Hematology Department, were included in the study. The patients were evaluated in two groups, with and without cardiotoxicity after AHSCT. We separated the frequency of cardiotoxicity that developed during hospitalization after transplantation and patients who developed and did not develop cardiotoxicity. We compare some parameters including gender, age, lymphoma type, stage, cardiac risk factors before transplantation, the number of chemotherapy cycles and the use of rituximab before the transplantation, radiotherapy before transplantation, Karnofsky performance scale, the amount of Dimethyl sulfoxide among these patients. Also, we evaluated patients with echocardiopraphy before transplantation and measured left ventricle ejection fraction (LVEF). We use CTCAE V 4.0 system for evaluating cardiotoxicity level from Grade I to Grade V. Results: Nine patients developed cardiac events. One patient developed Grade V MI and died despite treatment. Other eight toxicities developed Grade III-IV and returned by treatment. In terms of risk factors, LVEF of the group with cardiotoxicity was found to be significantly low (p < 0.05). There is no statistical difference between the two groups with other parameters. Conclusions: Cardiotoxicity is a frequent complication of autologous stem cell transplantation. A detailed pre-transplantation evaluation of all patents in terms of cardiac functions is essential to reduce cardiac morbidity. Therefore, patients should be evaluated cardiologically before transplantation and closely monitored for post-transplantation cardiac side effects. Some studies show that enalapril and carvedilol may be beneficial to prevent from cardiotoxicity. Although not in our routine, if approved by larger studies, it may be necessary to use agents such as enalapril and carvedilol in prophylaxis in reduce cardiotoxicity.